2000
DOI: 10.1128/aem.66.10.4173-4179.2000
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Escherichia coli and Listeria innocua in Milk by Combined Treatment with High Hydrostatic Pressure and the Lactoperoxidase System

Abstract: We have studied inactivation of four strains each of Escherichia coli and Listeria innocua in milk by the combined use of high hydrostatic pressure and the lactoperoxidase-thiocyanate-hydrogen peroxide system as a potential mild food preservation method. The lactoperoxidase system alone exerted a bacteriostatic effect on both species for at least 24 h at room temperature, but none of the strains was inactivated. Upon high-pressure treatment in the presence of the lactoperoxidase system, different results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 29 publications
1
47
0
Order By: Relevance
“…Results obtained by Garcia-Graells et al [16] also showed that adding LPS inhibited the growth of L. innocua in milk: no growth was observed for 24 h at 20 °C.…”
Section: Behavior Of L Monocytogenes In Milkmentioning
confidence: 85%
“…Results obtained by Garcia-Graells et al [16] also showed that adding LPS inhibited the growth of L. innocua in milk: no growth was observed for 24 h at 20 °C.…”
Section: Behavior Of L Monocytogenes In Milkmentioning
confidence: 85%
“…Furthermore, besides studies of the potential of "natural" preservative systems such as the LP system to increase the safety and extend the shelf-life of perishable foods and other products, studies are also needed to address the potential emergence of LP tolerance. Finally, our research group has previously reported that a sublethal treatment with high hydrostatic pressure strongly sensitizes bacteria to the LP system, opening perspectives for the application of this combined treatment for mild food preservation (9,10). The implications of the LP tolerance reported in the present work on the efficiency of this combined treatment should be further investigated.…”
Section: Discussionmentioning
confidence: 59%
“…The eVect of the addition of diVerent amounts of red wine on the survival of L. innocua in the stomach model L. innocua was chosen as a nonpathogenic model organism for L. monocytogenes. The suitability of L. innocua as a substitute for L. monocytogenes is based on the fact that it has been shown that both species behave in a similar manner when submitted to several diVerent types of environmental stresses (García-Graells, Valckx, & Michiels, 2000;Piyasena et al, 1998). In order to determine the inXuence of a red wine (total acidity of 5.9 g/L, volatile acidity of 0.64 g/ L and pH 3.59) on the survival of L. innocua NCTC 11288 during a simulated meal in a stomach model, assays were made with the addition of 30 mL, 60 mL and 130 mL of wine which, proportionally to the amount of food in the stomach model, correspond, approximately, to half a glass, a glass and half a bottle, respectively.…”
Section: Resultsmentioning
confidence: 99%